Transcriptional Profiling of Ileocecal Valve of Holstein Dairy Cows Infected with Mycobacterium avium subsp. Paratuberculosis - Hempel, Randy J. (PLoS One, 2016)
Johne’s disease is a chronic infection of the small intestine caused by Mycobacterium avium subspecies paratuberculosis (MAP), an intracellular bacterium. The events of pathogen survival within the host cell(s), chronic inflammation and the progression from asymptomatic subclinical stage to an advanced clinical stage of infection, are poorly understood. This study examines gene expression in the ileocecal valve (ICV) of Holstein dairy cows at different stages of MAP infection. The ICV is known to be a primary site of MAP colonization and provides an ideal location to identify genes that are relevant to the progression of this disease. RNA was prepared from ICV tissues and RNA-Seq was used to compare gene transcription between clinical, subclinical, and uninfected control animals. Interpretation of the gene expression data was performed using pathway analysis and gene ontology categories containing multiple differentially expressed genes. Results demonstrated that many of the pathways that had strong differential gene expression between uninfected control and clinical cows were related to the immune system, such as the T- and B-cell receptor signaling, apoptosis, NOD-like receptor signaling, and leukocyte transendothelial migration pathways. In contrast, the comparison of gene transcription between control and subclinical cows identified pathways that were primarily involved in metabolism. The results from the comparison between clinical and subclinical animals indicate recruitment of neutrophils, up regulation of lysosomal peptidases, increase in immune cell transendothelial migration, and modifications of the extracelluar matrix. This study provides important insight into how cattle respond to a natural MAP infection at the gene transcription level within a key target tissue for infection.